2(x-1)+ 3(x+1)=4(x+4)

Answers

The average is 85% my dude

to find the vertical asymptotes we solve the equation n(x) = 0. the vertical asymptotes are x = 1 and x = –1. to fund them solve the equation n(x) = 0. the numerator t(x) then the x axis is an asymptote.

x = 15

Step-by-Step Explanation:

In the given, we have three coefficients.

2 (x-1) + 3 (x+1) = 4 (x+4)

Distribute the coefficients to the terms in the (parenthesis) by multiplying them to the numbers and variables inside.

2x - 2 + 3x + 3 = 4x + 16

Move those with the variable x to the left and the whole numbers to the right. Keep in mind to use the opposite sign once these numbers went to the other side.

2x - 2 + 3x + 3 = 4x + 16

2x + 3x - 4x = 2 - 3 + 16

Add them starting the ones with the variables on the left.

2x + 3x - 4x = 2 - 3 + 16

5x - 4x = 2 - 3 + 16

x = 2 - 3 + 16

Then add the remaining terms, those constants (whole numbers) on the right.

x = 2 - 3 + 16

x = - 1 + 16

x = 15



Do you know the answer?

Other questions on the subject: Math

Math, 28.10.2019, 09330399672
it is no.3 because the students have been determined by it's quantity while others is a not well defined set because there is no such answer because you don't know if it is rich or...Read More
1 more answers
Math, 28.10.2019, abyzwlye
Im not sure of my answer because i suck at math but i would like to share my answer to help you a little bit.i think the answer is 6 days is my solution 5 x 12 divided by 10 and 6...Read More
2 more answers
Math, 28.10.2019, ShairaGailSanchez
i don’t know what the answer is i wish i could help...Read More
2 more answers